2021
DOI: 10.1021/acs.est.1c02689
|View full text |Cite
|
Sign up to set email alerts
|

Mass Absorption Efficiency of Black Carbon from Residential Solid Fuel Combustion and Its Association with Carbonaceous Fractions

Abstract: Black carbon (BC) emissions, derived primarily from incomplete fuel combustion, significantly affect the global and regional climate. Mass absorption efficiency (MAE) is one important parameter in evaluating the climate impacts of BC. Here, values and variabilities in the MAE of BC (MAEBC) from real-world residential emissions were investigated from a field campaign covering 163 burning events for different fuel–stove combinations. MAEBC (average: 12 ± 5 m2/g) was normally distributed and varied greatly by 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 88 publications
3
23
1
Order By: Relevance
“…No significant difference is found between the results for crop residue and wood (J. Sun et al., 2016; L. Zhang, Luo, et al., 2021). But a laboratory study by J.…”
Section: Brc Emission and Its Absorption Property From Different Sour...mentioning
confidence: 97%
See 4 more Smart Citations
“…No significant difference is found between the results for crop residue and wood (J. Sun et al., 2016; L. Zhang, Luo, et al., 2021). But a laboratory study by J.…”
Section: Brc Emission and Its Absorption Property From Different Sour...mentioning
confidence: 97%
“…For example, the study by Fan et al (2016) reported higher MAE WSOC for the combustion of crop than wood while trend is opposite in the study of Fan et al (2018), although both studies collected samples in a laboratory chamber simulating open burning in the field. Although studies have tested various types of stoves for the burning of biomass, for example, the traditional three-stone fire and a forced-draft fan type cookstove in M. Xie et al (2018), and metal stoves, built-in-place stoves and Kang in L. Zhang, Luo, et al (2021), no specific conclusion has been drawn regarding the influence of stove type on the MAE of BrC from biomass burning emission. Meanwhile, studies have shown that BrC MAE from residential biomass burning in stoves are greater than open biomass burning, implying higher temperature and more flaming combustion in stoves (M. Xie et al, 2018).…”
Section: Table 2 Continuedmentioning
confidence: 99%
See 3 more Smart Citations